2020
DOI: 10.3168/jds.2019-18025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of employer management on employee recruitment, satisfaction, engagement, and retention on large US dairy farms

Abstract: Lack of employee engagement and satisfaction and high turnover rate of employees are major problems on some US dairy farms. Farm adoption of human resource management (HRM) practices varies widely. Using feedback from 168 employees from 12 large dairy farms, our objectives were to understand employee perceptions of HRM strengths and weaknesses and their influence on (1) employee satisfaction, (2) retention of employees, (3) willingness of employees to recommend the farm as a place to work, and (4) level of emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…The controlling variables were the legal form, size of the enterprise from the point of view of the number of employees, region, and employee's criteria (age, length of work experience) which were chosen for the reason of their possible impact on the examined relationships based on existing studies. In the study of Moore et al (2020), the positive context of the position, employee's gender and employment duration in agricultural enterprises and their engagement was confirmed. Hakanen et al (2019) confirmed the connection between employee engagement and the size of the enterprise.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…The controlling variables were the legal form, size of the enterprise from the point of view of the number of employees, region, and employee's criteria (age, length of work experience) which were chosen for the reason of their possible impact on the examined relationships based on existing studies. In the study of Moore et al (2020), the positive context of the position, employee's gender and employment duration in agricultural enterprises and their engagement was confirmed. Hakanen et al (2019) confirmed the connection between employee engagement and the size of the enterprise.…”
Section: Methodsmentioning
confidence: 81%
“…Engaged employees also require, besides the direct support of their managers, the support of a culture built on trust and a feeling of freedom and the possibility to autonomously make decisions. Enterprises should respect this when setting the processes of human resource management, which complies with the recommendations of Moore et al (2020). Here, there a large space arises for the implementation of current approaches in people management in which a partner approach to the employees with a high rate of individualisation is preferred.…”
Section: Discussionmentioning
confidence: 96%
“…Based on its nature, employee recruitment methods are divided into 2, namely open recruitment and closed recruitment [4]. Open recruitment is a method held to attract potential candidates from the general public.…”
Section: Employee Recruitmentmentioning
confidence: 99%
“…Anyone who meets the criteria for a position is entitled to register and participate in the selection. This method allows many applications to come in, so the company or agency has a greater chance of getting qualified employees [4]. Unlike the open system, the closed system is only for certain candidates, so the number of applications that come in is less.…”
Section: Employee Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation